ANALISIS PERILAKU KONSUMEN TEHADAP KEPUTUSAN NASABAH DALAM MEMILIH PEMBIAYAAN MURABAHAH DI BMT AL HIDAYAH KAWALU TASIKMALAYA - Joni Joni; Yusep Rafiqi; Lina Marlina (Universitas Siliwangi, 2019)
Consumer decision making in selecting the financing of the dominant consumerbehavior, where consumer behavior is a process, and decision-making is one of the stages. There are many influences that underlie the consumer in choosing a murabaha financing at BMT. Decision-making customers in selecting the financing murabaha in BMT Al Hidayah influenced by several factors, including cultural, social, personal and psychological factors. This study aims to determine the influence of consumer behavior partially and simultaneously against the decision of the customers choose murabaha financing and which variables most affect the customer's decision to choose financing murabaha in BMT Al Hidayah KawaluTasikmalaya. The analysis showed that the variables of consumer behavior (cultural, social, individual, psychological) influence the customer's decision in choosing a murabaha financing amounted to 95.7% while the remaining 4.3% is influenced by other variables outside the research model.